Immunosuppressive medication adherence and affecting factors in solid organ transplantation patients: a mixed-methods study - Gündüz, Emine Selda; Kiraz, Nihal; Küçükkaya, Aycan; Göktas, Polat (The European Research Journal, 2024)
Objectives: Transplantation is a form of treatment that requires long-term pharmacotherapy. After transplantation, patients may have difficulty adapting to medication use for various reasons, and this may result in rejection. The aim of this study is to determine participants’ medication compliance and the factors affecting it. Methods: The research was conducted with a sequential explanatory mixed method. In the study, quantitative data were collected using the Turkish Immunosuppressive Medication Adherence Scale, and qualitative data were collected using the In-Depth Individual Interview Guide. Quantitative data were analyzed using statistical methods, and qualitative data were examined according to Braun and Clarke's thematic analysis framework. Results: In this study, 62.3% of the participants were male, 37.0% were 50 years old and over, 71.3% lived with their spouse, 54.0% had primary and secondary school education, and 42.0% could not work due to their current health condition. From a clinical perspective, it was determined that 78% of the transplants were kidney transplants, and 41.3% were more than 4 years after transplantation. 74.3% of the transplants were from living donors. The mean score of the immunosuppressive medication compliance scale was determined to be 40.91±4.09. In the qualitative data analysis of the study, factors affecting medication adherence were examined and the themes of "individual factors", "complexity of the regimen" and "social support resources" were obtained. The sub-themes of the individual factors theme are reluctance, hopelessness and addiction; Sub-themes of the complexity of the regimen theme are drug side effects and polypharmacy; The sub-themes of the social support resources theme are loneliness and family pressure. Conclusions: The factors influencing medication adherence among organ transplant recipients have been investigated, revealing that adherence levels vary significantly depending on various factors. These findings underscore the importance of tailored care strategies and individualized support approaches.